A Simplified Method Characterizing Magnetic Ordering Modulated Photo‐Thermoelectric Response in Noncentrosymmetric Semimetal Ca3Ru2O7. Issue 8 (13th May 2022) - Chen, Qiang; Li, Jialin; Zhu, Huanfeng; Zhang, Tian; Tang, Wei; Xing, Hui; Peng, Jin; Mao, Zhiqiang; Li, Linjun
Abstract : Recently, the spin entropy related to magnetic‐order transition, which contributes to thermoelectric power is attracting more and more attention. Here, it is demonstrated that the photo‐thermoelectric (PTE) response can be reshaped when Ca3 Ru2 O7 undergoes a meta‐magnetic phase (MMP) transition driven by both temperature and magnetic field. First, a sign change is observed crossing T S = 48 K and the linear polarization angle‐dependent PTE current maximizes along the a ‐axis above T S, while it maximizes along the b ‐axis below T S, which indicates that the antiferromagnetic spin order contributes to such spatial anisotropy. Second, in the temperature range of around 40–50 K, the PTE current is found to be sharply suppressed when the external magnetic field is applied in plane along the a ‐axis but is only gradually suppressed when the applied field is along the b ‐axis, which gives out two critical fields. Such suppression of PTE current under a magnetic field is attributed to the suppression of the spin entropy in the phase transition between the antiferromagnetic state and the MMP state and the H–T phase diagrams of Ca3 Ru2 O7 are redrawn accordingly. The work provides a convenient yet efficient method to understand the magnetic phase transition, which may also find applications in other correlated spin materials in general. Abstract : The photo‐thermoelectric (PTE) response is measured on the Ca3 Ru2 O7 single‐crystal device. Significant modulation in the PTE response is attributed to the contribution from spin entropy of the localized carriers in a certain magnetic ordering state. The critical points of d(PTE)/dH at different temperatures reconcile well with the boundary of the phase diagram drawn by previous research.